Pengaruh FOMO dan E-WOM Terhadap Perilaku Impulsive Buying pada Generasi Z yang Bekerja - Elin Rahmadhani; Fidia Oktarisa (INDO PUBLISHING, 2025)
This study aims to examine the influence of Fear of Missing Out (FOMO) and Electronic Word of Mouth (E-WOM) on impulsive buying behavior among working Generation Z individuals. This study employs a quantitative approach with a correlational design. The sampling technique used purposive sampling through a Google Form questionnaire involving Generation Z workers. The research instruments utilized a Likert scale, including the Impulsive Buying Tendency (IBT) scale, the FOMO scale, and the E-WOM scale. The study employed multiple linear regression analysis, which revealed that FOMO and E-WOM, both individually and simultaneously, significantly influence impulsive buying behavior. The contribution of these two variables in explaining impulsive buying is 27.9%, while the remaining 72.1% is influenced by other variables not included in this study.